East into Upper East plain tales from New York and New Delhi - Jhabvala, Ruth Prawer 1927-2013 (Counterpoint, 1998)
Stories featuring cosmopolitan Indians. In Independence, set in India, a high-class woman earns a living teaching social graces, in Two Muses, set in London, a girl observes her grandfather's marital infidelity, and in A Summer by the Sea, set in New York, a woman falls for the lover of her homosexual son-in-law.
Keywords: Alltag, Brauchtum; New Delhi (India) -- Social life and customs -- Fiction; New York (N.Y.) -- Social life and customs -- Fiction